2005
DOI: 10.1091/mbc.e04-06-0498
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Properties of the Nonhelical Tail Domain in Type II Keratin 5: Insight from a Bullous Disease-causing Mutation

Abstract: Inherited mutations in the intermediate filament (IF) proteins keratin 5 (K5) or keratin 14 (K14) cause epidermolysis bullosa simplex (EBS), in which basal layer keratinocytes rupture upon trauma to the epidermis. Most mutations are missense alleles affecting amino acids located in the central ␣-helical rod domain of K5 and K14. Here, we study the properties of an unusual EBS-causing mutation in which a nucleotide deletion (1649delG) alters the last 41 amino acids and adds 35 residues to the C terminus of K5. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 72 publications
(134 reference statements)
2
17
0
1
Order By: Relevance
“…The mammalian expression constructs pEGFP-C3 K5 (16) and pEGFP-C3 K17 (17) have been described. AnxA2 cDNA was cloned out of pOTB7 AnxA2 (ATCC) using PCR with the primers 5Ј-AGTCGACGATGTCTACTG TTCACG-3Ј (forward) (with a SalI restriction site underlined) and 5Ј-GTGGATCCTCAGTCA-TCTC CACC-3Ј (reverse) (with a BamHI restriction site underlined) and cloned into mCherry-C1 (Clontech, Mountain View, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The mammalian expression constructs pEGFP-C3 K5 (16) and pEGFP-C3 K17 (17) have been described. AnxA2 cDNA was cloned out of pOTB7 AnxA2 (ATCC) using PCR with the primers 5Ј-AGTCGACGATGTCTACTG TTCACG-3Ј (forward) (with a SalI restriction site underlined) and 5Ј-GTGGATCCTCAGTCA-TCTC CACC-3Ј (reverse) (with a BamHI restriction site underlined) and cloned into mCherry-C1 (Clontech, Mountain View, CA).…”
Section: Methodsmentioning
confidence: 99%
“…For the EBS-localized, EBS-generalized, and EBS-DM variants, a strong concordance exists among the position and nature of the mutation in the target keratin protein, the extent to which it disrupts keratin IF assembly and structure (when tested in vitro or through transfection in cultured cells), and, ultimately, the severity of clinical presentation (52)(53)(54)(55)(56)(57). A corollary to this principle is that the nature of the mutation affecting K5 or K14 defines the sensitivity threshold that the epithelium displays toward frictional trauma, thereby contributing to whether the symptoms are local (e.g., EBS-localized) or generalized (e.g., EBS-generalized and EBS-DM).…”
Section: Some Key Lessons Learned From Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Additional studies confirmed that the cell fragility seen in EBS corresponds to a loss-of-function phenotype. Key among them were the severe epithelial blistering phenotype exhibited by K14-and K5-null mice (Lloyd et al 1995;Peters et al 2001), the finding that disease-causing mutations in either K5 or K14 markedly weaken the mechanical resilience of K5-K14 filament assemblies in vitro Gu and Coulombe 2005) and affect de novo IF network formation in live keratinocytes (Werner et al 2004), and the realization that EBS disease severity correlates with the impact of K5 or K14 mutations on IF assembly in vitro (e.g., see Letai et al 1993).…”
Section: Cytoplasmic Ifs and Mechanical Support: A Matter Of Integritymentioning
confidence: 99%